Strategic management and activity-based costing - Manalo, R. G. (Animo Repository, 2010)
This paper introduces a framework that could change the way firms set their strategies and goals. This framework links corporate budget to corporate strategies which are cascaded down to the last employee. It bridges the gap between operations personnel and finance people as they talk of only the jargon of activity or process costs. It is flexible as it can increase or decrease the budget from the corporate down to the smallest unit of the firm when the focus or goals of the company change within the period. It is an effective tool to predict future budgets and operations of the company as it uses activity costs which are more accurate than the traditional method of forecasting. It balances the profit maximization goal of a firm with that of the company's culture or shared values and societal expectations especially environmental protection, customer satisfaction and employee welfare. ©2010 IEEE.